2011
DOI: 10.1242/jeb.056499
|View full text |Cite
|
Sign up to set email alerts
|

The development of endotoxin tolerance, and the role of hypothalamo-pituitary-adrenal function and glucocorticoids in Pekin ducks

Abstract: SUMMARYEndotoxin tolerance represents a state of abated immunological responsiveness to pyrogens, which, in mammals, leads to the decline or abolition of the fever response. The development of endotoxin tolerance in birds is not well understood; consequently, the impact of repeated pathogenic exposure on the avian febrile response, and thus on the ability of birds to fight recurrent infection, is not known. We determined the effect of repeated injections of lipopolysaccharide (LPS) on the febrile response of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
3
11
2
Order By: Relevance
“…In the current study, no tolerance was observed, since no significant decrease was observed for LPS primary stimulated cells in the surface expression of the activation markers CD40 and MHC-II nor NO production upon secondary stimulation with LPS. The fact that we did not find evidence of LPS-induced tolerance in the current study contrasts with other in vivo studies in birds [38,39]. At this moment we are not able to clarify the absence of the tolerogenic state of the LPS primary stimulated cells.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, no tolerance was observed, since no significant decrease was observed for LPS primary stimulated cells in the surface expression of the activation markers CD40 and MHC-II nor NO production upon secondary stimulation with LPS. The fact that we did not find evidence of LPS-induced tolerance in the current study contrasts with other in vivo studies in birds [38,39]. At this moment we are not able to clarify the absence of the tolerogenic state of the LPS primary stimulated cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous exposure to LPS does not affect the body temperature response during a second LPS injection when injections are more than 2 weeks apart (at least in Pekin ducks; Marais et al, 2011b). This was true also in our study ( previous LPS dose: P=0.61).…”
Section: Methodssupporting
confidence: 82%
“…Therefore in the present study, LPS from Escherichia coli 055:B5 was used, which was induced only transient fever, vomiting and diarrhea. Although repeated administration of LPS developed an adaptive response in a set of behaviors (such as the febrile response), which was similar to the results of previous studies (36,37), it did induce a system inflammatory response and increase in the inducibility of AF.…”
Section: Discussionsupporting
confidence: 87%